2022
DOI: 10.1177/17470218221126416
|View full text |Cite
|
Sign up to set email alerts
|

Market mindset hinders interpersonal trust: The exposure to market relationships makes people trust less through elevated proportional thinking and reduced state empathy

Abstract: In a series of five experiments, we provided evidence that evoking the market mindset negatively affects trust. We found that the market mindset reduces trust compared to the communal mindset (Experiment 1) and a neutral condition (Experiment 2). Next, we examined the psychological mechanisms behind the detrimental effect of the market mindset on trust and found that this effect was mediated by enhanced proportional thinking (Experiments 3 and 4) and reduced state empathy (Experiments 4 and 5). Finally, in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 110 publications
0
8
1
Order By: Relevance
“…Previous research has documented that adopting the market mindset can negatively affect interpersonal trust (Kuzminska, Gasiorowska, & Zaleskiewicz, 2023; Xin & Xin, 2017). In contrast to those earlier results, in this project, we aimed to show that they are not necessarily universal, as the nature of the effect of the market mindset may depend on the characteristics of the situation that calls for trust.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has documented that adopting the market mindset can negatively affect interpersonal trust (Kuzminska, Gasiorowska, & Zaleskiewicz, 2023; Xin & Xin, 2017). In contrast to those earlier results, in this project, we aimed to show that they are not necessarily universal, as the nature of the effect of the market mindset may depend on the characteristics of the situation that calls for trust.…”
Section: Discussionmentioning
confidence: 99%
“…Having this in mind, we decided to perform Experiment 2 using a wide online study sample to ensure that participants were indeed anonymous to each other. Last, we opted to employ a different method for manipulating the market mindset, which has been successfully used in previous research (e.g., Kuzminska, Gasiorowska, & Zaleskiewicz, 2023; Zaleskiewicz et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, certain studies revealed that exposing individuals to market relations or reminding them of their shopping experiences facilitated their proportional thinking, competitiveness, and self-interest (Bauer et al, 2012;Zaleskiewicz et al, 2020). In other words, individuals' participation in the market typically results in the acquisition of a self-interested and rational market mindset (Olga Kuzminska et al, 2022), which may ultimately influence their prosocial behaviours. Social mindfulness is a common prosocial behaviour in daily life that stands apart from other prosocial behaviours due to its low-cost nature.…”
Section: R E G U L a R A R T I C L Ementioning
confidence: 99%